Dakwah Sinkretis Sunan Kalijaga - Supriyanto Supriyanto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
Sunan Kalijaga is one figure from Walisongo that often reconcile Islam with reality. He didn’t destroy tradition orculture. Otherwise, he modifies content and core inside it with Islamic values. This effort often calls as syncretism, or in Gus Durterm ‘pribumisasi’. Wayang tradition, that still exists today amongst Javanese society, actually Hindu-Buddha tradition beforeIslam’s encountering. But with his wit, Sunan Kalijaga was able to insert new content to that tradition, namely Islamic values.